1999
DOI: 10.1159/000054432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Blockade of Catecholaminergic Alpha and Beta Receptors on Histamine-Induced Release of Corticotropin and Prolactin

Abstract: We investigated the role of adrenergic receptors in histamine (HA)-induced release of corticotropin (ACTH) and prolactin (PRL) in conscious male rats. Specific α- or β-receptor antagonists were administered intracerebroventricularly in doses of 1 mmol at time –20 min, and HA (270 nmol), the H1 receptor agonist 2-thiazolylethylamine (2-TEA; 2,180 nmol) or the H2 receptor agonist 4-methylHA (4-MeHA; 790 nmol) were administered intracerebroventricularly at –15 min. The animals were decapitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
1
1
Order By: Relevance
“…We have recently reported that blockade of a1 or b1 adrenoreceptors inhibited the PRL response to central administration of HA whereas the ACTH response to HA remained unaffected during central pretreatment with selective or non-selective a or b adrenoreceptor antagonists (17). Compared with the present study, we suggest that catecholamines and histamine interact in the central regulation of PRL secretion whereas the transmitters do not exert synergistic actions in the central regulation of ACTH secretion.…”
Section: Figurecontrasting
confidence: 75%
See 1 more Smart Citation
“…We have recently reported that blockade of a1 or b1 adrenoreceptors inhibited the PRL response to central administration of HA whereas the ACTH response to HA remained unaffected during central pretreatment with selective or non-selective a or b adrenoreceptor antagonists (17). Compared with the present study, we suggest that catecholamines and histamine interact in the central regulation of PRL secretion whereas the transmitters do not exert synergistic actions in the central regulation of ACTH secretion.…”
Section: Figurecontrasting
confidence: 75%
“…We have recently found that specific blockade of a1 and b1 adrenergic receptors inhibited the HA-induced PRL response (17), suggesting that HA interacts with catecholamines via these receptor subtypes in the regulation of PRL secretion. In contrast, we found that the ACTH response to HA was not affected by blockade of adrenergic receptors.…”
Section: Introductionmentioning
confidence: 97%